Enhancing Numeracy Literacy of Deaf Students: Developing Problem-Based Learning with Realistic Mathematics Education Assisted By E-Comic - Valda Nafila; Sugiman Sugiman (AL-ISHLAH: Jurnal Pendidikan, 2026)
Numeracy literacy is a crucial 21st-century competency, yet deaf students often face significant challenges in understanding abstract mathematical concepts due to communication limitations. This study aims to develop and produce an E-Comic based on Realistic Mathematics Education (RME) integrated with a Problem-Based Learning (PBL) model to enhance the numeracy literacy of deaf students. This Research and Development (RD) study adapted the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted with a sample of 5 deaf students at the junior high school level at SLB BC YMS Wonogiri. Data were collected using numeracy literacy tests, validity questionnaires, and teacher and student response questionnaires to measure practicality. The results demonstrate that the developed e-comic is highly valid, achieving an average validity score of 89.02%. In terms of practicality, the media received an average score of 82.19% from teachers and students. Furthermore, the e-comic proved to be effective in improving numeracy literacy, as evidenced by an N-Gain score of 0.77, which falls into the high improvement category. Therefore, realistic mathematics education based e-comics with a problem based learning model is a valid, practical, and effective learning medium that significantly improves the numeracy literacy skills of deaf students.